2017
DOI: 10.14814/phy2.13238
|View full text |Cite
|
Sign up to set email alerts
|

No effect of ascorbate on cutaneous vasodilation and sweating in older men and those with type 2 diabetes exercising in the heat

Abstract: Aging and chronic disease such as type 2 diabetes (T2D) are associated with impairments in the body's ability to dissipate heat. To reduce the risk of heat‐related injuries in these heat vulnerable individuals, it is necessary to identify interventions that can attenuate this impairment. We evaluated the hypothesis that intradermal administration of ascorbate improves cutaneous vasodilation and sweating in older adults via nitric oxide synthase (NOS)‐dependent mechanisms during exercise in the heat and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
8
12
2
Order By: Relevance
“…Intriguingly, contemporary studies utilizing intradermal administration of ascorbate in both young and old adults exercising in the heat reported no significant elevations in CVC, as opposed to the earlier study by Holowatz and colleagues . This discrepancy was postulated to be contributed by the difference in T sk of the subjects during ascorbate administration in both studies.…”
Section: Age‐associated Impairments In Thermoregulatory Functioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Intriguingly, contemporary studies utilizing intradermal administration of ascorbate in both young and old adults exercising in the heat reported no significant elevations in CVC, as opposed to the earlier study by Holowatz and colleagues . This discrepancy was postulated to be contributed by the difference in T sk of the subjects during ascorbate administration in both studies.…”
Section: Age‐associated Impairments In Thermoregulatory Functioncontrasting
confidence: 64%
“…In the latter study, passive heating of subjects, using a water‐perfused thermal suit could have prompted a comparatively greater rise in T sk as well as cutaneous oxidative stress . On the other hand, owing to the relatively moderate mean T sk achieved (≈35 °C) when subjects exercised in a hot and dry environment in the former study, resultant levels of oxidative stress could have been insufficient to induce significant alterations in cutaneous vascular response despite treatment with ascorbate . While evidence supporting this notion remains indirect, this association appears to be corroborated by an increase in oxidative marker, malondialdehyde (MDA), when young adults exercised under hot and humid ambient conditions as compared to temperate conditions …”
Section: Age‐associated Impairments In Thermoregulatory Functionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, T2D is a well‐established risk factor for cardiovascular disease (Gu, Cowie, & Harris, ) and is associated with endothelial dysfunction, as reflected by impaired Acetylcholine‐induced forearm vasodilatation (Mäkimattila et al., ; Woodman, Watts, Playford, Best, & Chan, ). In addition, T2D is associated with altered cutaneous vascular (microvascular) responses (Caballero et al., ; Colberg, Stansberry, McNitt, & Vinik, ; Sokolnicki, Roberts, Wilkins, Basu, & Charkoudian, ), although this is not always observed, especially when evaluated in relatively healthy individuals with well‐controlled T2D and free of co‐morbidities such as peripheral neuropathy (Fujii et al., ; Sokolnicki et al., ). To date, there remains a paucity of information on how, if at all, T2D might modulate the mechanisms regulating cutaneous blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in nitric oxide bioavailability in individuals with type 2 diabetes is well established [62,63,72,73] and may be further exacerbated by the presence of atherosclerotic plaques which are known to adversely alter endothelial function through interfering with nitric oxide signaling [74]. In fact, one study reported that the relative nitric oxide-dependent vasodilation during whole-body passive heating was similar between healthy controls and type 2 diabetics; however, absolute SkBF was lower in the latter group [72].…”
Section: The Mechanisms Underlying Type 2 Diabetes-related Impairmentmentioning
confidence: 99%